Improving the quality of insulin prescribing for people with diabetes being discharged from hospital. Issue 3 (24th August 2019) - Bain, Amie; Silcock, Jon; Kavanagh, Sallianne; Quinn, Gemma; Fonseca, Ines
Abstract : Medication errors involving insulin in hospital are common, and may be particularly problematic at the point of transfer of care. Our aim was to improve the safety of insulin prescribing on discharge from hospital using a continuous improvement methodology involving cycles of iterative change. A multidisciplinary project team formulated locally tailored insulin discharge prescribing guidance. After baseline data collection, three 'plan-do-study-act' cycles were undertaken over a 3-week period (September/October 2018) to introduce the guidelines and improve the quality of discharge prescriptions from one diabetes ward at the hospital. Discharge prescriptions involving insulin from the ward during Monday to Friday of each week were examined, and their adherence to the guidance measured. After the introduction of the guidelines in the form of a poster, and later a checklist, the adherence to guidelines rose from an average of 50% to 99%. Qualitative data suggested that although it took pharmacists slightly longer to clinically verify discharge prescriptions, the interventions resulted in a clear and helpful reminder to help improve discharge quality for the benefit of patient safety. This project highlights that small iterative changes made by a multidisciplinary project team can result in improvement of insulin discharge prescription quality. The sustainability and scale of the intervention may be improved by its integration into the electronic prescribing system so that all users may access and refer to the guidance when prescribing insulin for patients at the point of discharge.